Seeing Jung’s Shadow in a New Light: Decolonizing the Undisciplined Depths - Daniel Boscaljon (Religions)
This paper explores two paths that depth psychology, particularly the work of C. G. Jung, offers to the project of decolonizing knowledge. Jung was a complex intellectual pioneer who embodied and projected the limiting colonialist scientific presuppositions of his time also spent much of his career attempting to become familiar with the undisciplined domain of the Unconscious that offered access to ways of thinking that erased disciplinary boundaries that would separate psychology, religion, and science. Offering a close reading of Jung’s early work demonstrates how colonizing forms of knowledge perpetuate themselves through a self-legitimating mythic structure. Acknowledging Jung’s later work, which explored psyche as both “material” and “spiritual”, illustrates the potential that depth psychology offers for an undisciplined approach to thinking and reality. The focus throughout will be on the Shadow, one of the core archetypes in Jungian psychology. The first section, which associates Jung’s colonial bias with his ideas about rational consciousness, is followed by a second section that provides a critique of Jung’s colonialism, highlighting the implicit violence that accompanies Jung’s story about rationality. The third section provides an overview of different ways that shadows can be used, building on other depth psychological modes of exploring the unconscious. The paper concludes with a description of how embracing Shadow invites the concept of an undisciplined playfulness back into a decolonized, experiential approach to knowledge. This presents an improved version of the Shadow based on a framework of participation, rather than polarization, which opens a mode of belonging that bridges rifts that colonialism created. This demonstrates how depth psychology opens a path toward decolonizing knowledge and moving toward a consciously undisciplined form of experiential understanding.